الجمعيات و مأسسة العمل الدعوي جمعية الإرشاد والإصلاح بولاية خنشلة أنموذجا - جدعون، زينة (University Of Eloued جامعة الوادي, 2024)
هدفت هذه الورقة العلمية والموسومة بـ "الجمعيات ومؤسسة العمل الدعوي جمعية الإرشاد والإصلاح أنموذجا بولاية خنشلة" إلى التعرف على العمل الدعوي في الجمعيات، خاصة ونحن نعيش عصر السموات المفتوحة وتمدد الإعلام في سياقات مختلفة خصوصا السياق الاجتماعي والديني والذي أفرز أجيالا تعيش في الواقع الافتراضي أكثر من العالم الواقعي، والخوف كل الخوف على فئة الأطفال والتي تركز عليها جمعية الإرشاد والإصلاح فرع ولاية خنشلة حيث تبين أن الجمعية تهتم بتعليم الأطفال القرآن الكريم واللغة العربية وتعاليم الدين الإسلامي، وتضمين كل أنشطتها للدعوة الإسلامية وتستهدف أكثر فئة الأطفال مع التركيز على عائلاتهم والتوجه بالدعوة إلى كل أفراد المجتمع خصوصا في المناسبات الاجتماعية والدينية؛ وما لاحظناه هو عدم تضمين التكنولوجيا لعملها خصوصا ونحن نعرف مدى أثرها وفعاليتها في هذا المجال. Abstract: This scientific paper, tagged "Associations and the institutionalization of advocacy work - the Guidance and Reform Association as a model in the state of Khenchela", aimed to identify advocacy work in associations, especially as we live in the era of open skies and the expansion of media in different contexts, especially the social and religious context, which produced generations living in virtual reality more than the real world, and fear is all fear for the category of children, which the Reform and Guidance Association, Khenchela Province, focuses on, where it was found that the association focuses on teaching children the Holy Quran. The Arabic language and the teachings of the Islamic religion, and the inclusion of all its activities in the Islamic call and targeting more children with a focus on their families and addressing the call to all members of society, especially in social and religious events; What we have noticed is that technology is not included in its work, especially as we know how effective it is in this area.
مداخلة
Keywords: الجمعيات; مؤسسة العمل الدعوي; جمعية الإصلاح والإرشاد; associations; institutionalization of advocacy work; reform and guidance association.